Hyperuricemia prevalence in healthy subjects and its relationship with cardiovascular target organ damage - Maloberti, Alessandro; Qualliu, Esmerilda; Occhi, Lucia; Sun, Jinwei; Grasso, Enzo; Tognola, Chiara; Tavecchia, Giovanni; Cartella, Iside; Milani, Martina; Vallerio, Paola; Signorini, Stefano; Brambilla, Paolo; et al. (Nutrition, metabolism, and cardiovascular diseases, 2021)
Heterogeneous results have been obtained in the relationship between Uric Acid (UA) and Target Organ Damage (TOD). In the present study we sought to assess the prevalence of hyperuricemia in healthy subjects as well as the role of UA in determining TOD. We evaluated vascular, cardiac and renal TODs in the whole population as well as sub-grouped by gender. As many as 379 blood donors participated at the present analysis. TOD was evaluated as Pulse Wave Velocity (PWV), Left Ventricular Mass Index (LVMI) and carotid Intima-Media Thickness (IMT). Hyperuricemia was defined with the classic cut-off (>7.0 in men and >6.0 mg/dL in women) but also with a most recently defined one (5.6 mg/dL for both sex). Hyperuricemia was present in 6.3% of the whole population (7.3% males, 2.8% females) considering the classic cut-off, while, with the recently identified one, it was present in 28.2% of the whole population (37.3% males, 4.7% females). Despite all the evaluated TODs significantly correlated with UA, linear multivariate regression analysis showed that none of them, except for GFR, displayed UA as a significant covariate. Similar figures were found also when both correlation and linear regression analyses were repeated in the two genders separately. Hyperuricemia is an important problem also in healthy subjects and its prevalence could further increase if lower cut-off will be used. In this specific population UA is significantly associated with renal impairment while this was not the case for cardiac and vascular damage. •Heterogeneous results have been obtained in the relationship between UA and TOD.•Multivariate analysis showed that only GFR, displayed UA as a significant covariate.•Hyperuricemia is prevalent also in healthy subjects and it could further increase if lower cut-off will be used.